2015
DOI: 10.1007/s11136-014-0908-0
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Activation Measure: a validation study in a neurological population

Abstract: The PAM-13 is an internally reliable and valid tool for research purposes. The use of categorical activation "level" in clinical settings should be done with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 40 publications
1
42
1
Order By: Relevance
“…This finding is similar to the explaining variance calculated in the German study (40.9 %) and in the Norwegian one (37.94 %) thus suggesting that additional factors explaining variance may be considered. This hypothesis is also embraced by studies carried on the neurological population [ 22 , 31 , 53 ]. The latter study performed a confirmatory factory analysis and suggested a tri-factor solutions as the optimal one.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is similar to the explaining variance calculated in the German study (40.9 %) and in the Norwegian one (37.94 %) thus suggesting that additional factors explaining variance may be considered. This hypothesis is also embraced by studies carried on the neurological population [ 22 , 31 , 53 ]. The latter study performed a confirmatory factory analysis and suggested a tri-factor solutions as the optimal one.…”
Section: Discussionmentioning
confidence: 94%
“…The transformation is based on the new index-scale by Insignia [ 24 ]. PAM has been validated among several patient groups with various chronic diseases [ 15 , 25 27 ]. In this study, we used the Norwegian back-translated PAM [ 28 ], which has been validated in mental health populations [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has demonstrated that psychometrically, the PAM 13 has stronger and more detailed all round validity in demonstrating clear face, content, construct and criterion validity and psychometric reliability across populations (14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). A large body of evidence therefore demonstrates that the PAM-13 is a valid, reliable and clinically useful measure of patient activation that can be used across diverse cultures and patient groups.…”
Section: Limitations Of the Promsmentioning
confidence: 98%
“…The PAM 13, a short-form version of the PAM 22, has been more extensively examined for use in additional populations and languages (14) . It offers strong psychometric evidence in people living with long term conditions (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The PAM; specifically the PAM-13, possesses a large body of evidence that supports its strong psychometric properties across diverse cultures and patient groups.…”
Section: Introductionmentioning
confidence: 99%